Anak Sebagai Enemy Combatant Dalam Hukum Humaniter - Uktolseja, Juniar Sammy; Peilouw, Johanis Steny Franco; Hanafi, Irma Halimah (TATOHI: Jurnal Ilmu Hukum, 2024)
Introduction: Children are the successor to the nation's generation. Children need physical and mental protection. Human rights are human rights since birth. Some countries, make children as objects of crime; ter violence.Purposes of the Research: To understand and analyze whether children as enemy combatants can be justified by humanitarian law, and to find out and describe legal protection for children as enemy combatants in accordance with humanitarian law.Methods of the Research: The research method is used to find and process data according to the research objectives and solve the problems raised by researchers.Results of the Research: The war that occurred resulted in many casualties and damage to the country's infrastructure. Children are victims of war, they don't know why war happened. Child participation in con. Children who are involved in armed conflicts and fall into the hands of enemies, then children who are held captive are entitled to special protection as stated in the third Geneva Convention of 1949. Humanitarian law.